Integration of Permaculture to Reinvent Students' Interest in Nature and Environmental Awareness for Quality Education under SDG-4 - Saefudin, Saefudin; Kusnadi; Tri Suwandi; Najira; Rahmat Baharudin; Hening Triandika Rachman (Jurnal Pendidikan IPA Indonesia, 2025)
Indonesia faces major environmental degradation challenges, so students’ interest in nature and environmental awareness are needed. Permaculture is an artificial ecosystem that promotes sustainable agricultural practice. Integrating permaculture into education can enhance students’ interest in nature and environmental awareness. However, a limited study has explored its practical application in educational settings. This study aims to examine the effect of permaculture integration in education on students’ interest in nature and environmental awareness, which can support the achievement of quality education according to SDG-4. This study used a quantitative approach with a quasi-experimental design. The instruments used were a scale to measure students’ interest in nature and essay tests to measure students’ environmental awareness. Data were analyzed using the Mann-Whitney U test (U = 0.28) and independent sample t-test (p = 0.40). The results showed that although there was no significant difference between the experimental and control groups regarding interest in nature and environmental awareness, this study is still important. Based on the scale of interest in nature, most students showed high emotional, cognitive, and value aspects. However, significant increases in environmental interest and awareness have not yet been achieved, indicating that permaculture-based learning requires a long-term period to provide a more tangible impact. It can be concluded that integrating permaculture into education can reinvent students’ interest and environmental awareness.